Effects of Reward Contingencies on Brain Activation During Feedback Processing - Yi eJiang; Sung-il eKim; Mimi eBong (Frontiers in Human Neuroscience, 2014)
This study investigates differential neural activation patterns in response to reward-related feedback depending on various reward contingencies. Three types of reward contingencies were compared: a ‘gain’ contingency (a monetary reward for correct answer/no monetary penalty for incorrect answer); a ‘lose’ contingency (no monetary reward for correct answer/a monetary penalty for incorrect answer); and a ‘combined’ contingency (a monetary reward for correct answer/a monetary penalty for incorrect answer). Sixteen undergraduate students were exposed to the three reward contingencies while performing a series of perceptual judgment tasks. The fMRI results revealed that only the ‘gain’ contingency recruited the ventral striatum, a region associated with positive affect and motivation, during overall feedback processing. Specifically, the ventral striatum was more activated under the ‘gain’ contingency than under the other two contingencies when participants received positive feedback. In contrast, when participants received negative feedback, the ventral striatum was less deactivated under the ‘gain’ and ‘lose’ contingencies than under the ‘combined’ contingency. Meanwhile, the negative feedback elicited significantly stronger activity in the dorsal amygdala, a region tracking the intensity and motivational salience of stimuli, under the ‘gain’ and ‘lose’ contingencies. These findings suggest the important role of contextual factor, such as reward contingency, in feedback processing. Based on the current findings, we recommend implementing the ‘gain’ contingency to maintain individuals’ optimal motivation.